Health Literacy Health Behavior and Quality of Life of Phuket Village Health Volunteers - หล่อโลหการ สุวรรณา; นรินทร์รักษ์ ประพรศรี (Journal of Health Science of Thailand, 2021)
This objectives of this mixed methods research were to study health literacy, health behaviors based on the 3E2S concept and mental health status of Phuket’s village health volunteers; and to assess the correlation and factors influencing demography, enabling factors, reinforcing factors, health behaviors and quality of life; as well as to propose the guidelines for potential development according to roles of village health volunteers. Data were collected from 286 village health volunteers by using questionnaire. The participants were selected for focus group discussion during March to July 2019. The results of this study indicated that village health volunteers’ health literacy were at very good level (21.68%), good level (47.20%), health behaviors were at very good level 59.79%, mental health level was better than general people (28.32%), and good quality of life 61.19%. Factors influencing health behaviors were health literacy, sex, and source of income with multiple correlation coefficient of 0.459 which could explain the variance of overall of village health volunteers health behaviors, up to 19.30%. Moreover, factors influencing quality of life were mental health level, health literacy, education level, and time of work with multiple correlation coefficient of 0.639 which could explain the variance of overall of village health volunteers quality of life up to 39.50%. The finding revealed that health literacy influenced health behaviors and quality of life. By making the right decision making, accessing the information and health services correlated with Phuket’s village health volunteers with multiple correlation coefficient 0.368 and could explain up to 12.60% of health behaviors.